KLEOTERAPI ENDOSKOPI GETAH POHON PISANG SERTA MANFAATNYA DALAM MENYEMBUHKAN LUKA (KAJIAN SURAT AL WAAQI’AH : 25-33) - Liliek Harianie A.R, M.Djamhuri (lp2m-uin malang, 2006)
Banana (Musa acuminata) is one of the famous fruit plants in Indonesia. This fruit is very useful because of the nutrient content and biological effect such as cure many desease like : fever, digestion system. Almost all part of this plant can be use by human, leaf, trunk, flower even outgrowth. This research to study the sap from banana’s trunk to cure the wound. We use mus (Mus musculus) as the sample. The sample was treated using injure medicine usually used to compare with effect of sap from banana’s trunk. The bio active consist from sap banana’s trunk are : saponin, antraquinone, quinone, lectin and galat acid. These compounds were estimated have antifungi and antibacterial effect, decrease wide concentration of cholesterol blood and inhibit cancer cell growth. Result of the study showed that the wound treated with banana’s trunk sap has recovery injure and epitel cell regeneration faster than wound untreated even treated with injure medicine. This because the bio active contain from banana’s trunk sap saponin and tannin has antiseptic effect, antraquinone as antibiotic and reduce pain. Another compound, lectin stimulated the growth of new tissue from skin.